Empirical factors affecting memory in collaborative versus nominal groups - Guynn, Melissa J. (Frontiers in Psychology, 2024)
When individuals collaborate to try to retrieve some encoded information, not surprisingly, the collaborative group typically remembers more than does any individual. When the nonredundant output from the individuals is combined, however, this nominal group often, surprisingly, remembers more than does the collaborative group. This finding is known as collaborative inhibition. The finding of collaborative inhibition, that collaborative groups remember less would be predicted given the summed non-redundant memories of an equal number of individuals remembering alone, indicates that there is something about remembering in a collaborative group that impairs the performance of the individuals in that group. Research directed toward what that something is has focused on both social and cognitive factors, with the consensus being that cognitive factors play the more important role. An extensive body of work on this topic has accumulated over the past 25+ years, with researchers proposing theoretical explanations and generating empirical data revealing the conditions under which this collaborative inhibition is more versus less likely to occur. The purpose of this review is to summarize those empirical factors to provide a resource for researchers interested in pursuing this work.